Kendala Program Zakat Community Development BAZNAS Dalam Pengentasan Kemiskinan di Nagari Balai Baiak Malai III Koto - Haziratul Hidayati; Indraddin; Bob Alfiandi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Zakat is a philanthropic instrument that plays a role in poverty alleviation, one of which is through the Zakat Community Development (ZCD) Program managed by BAZNAS. This program aims to improve community welfare through village community empowerment and has been successful in several areas. However, in Nagari Balai Baiak Malai III Koto, the ZCD program has not shown the expected results. The target group is still classified as poor families, even the poverty rate has increased after the program runs.. So this research aims to identify the obstacles faced in poverty alleviation in nagari balai baiak malai iii koto. The research method used is a qualitative method with a case study type. The results of this study found that structural, institutional, socio-cultural, and political participation weaknesses are the main factors that hinder the success of the program. To improve the effectiveness of the program, synergy between BAZNAS and local government, community capacity building, local institutional strengthening, and transparency in the management of zakat funds are needed. With a more integrated approach, the program is expected to run more sustainably and have a positive impact in alleviating poverty. Keywords: Constraints, Philanthropy, Poverty Alleviation, Zakat Community Development